AgCuNi multi-element brazing filler metal as well as preparation method and brazing process thereof

By using AgCuNi multi-component solder, the high-quality connection between tantalum and Q345R steel is achieved by reacting Ni elements with Ta, which solves the problems of complexity and high cost of traditional welding methods, and improves the strength and corrosion resistance of the welded joints.

CN119772450AActive Publication Date: 2025-04-08NORTHWEST INSTITUTE FOR NONFERROUS METAL RESEARCH

Patent Information

Application Number
CN202510220784.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-04-08
Estimated Expiration
2045-02-27

AI Technical Summary

Technical Problem

It is difficult to achieve high-quality connection between tantalum and Q345R steel in the prior art. Traditional welding methods have problems such as complex process, high cost and great environmental damage. The AgCuTi solder prepared by powder metallurgy has problems such as oxidation, segregation and high brittleness of Ti elements.

Method used

AgCuNi multi-component solder is used to achieve brazing connection through reaction between Ni elements and Ta, and solid solution diffusion occurs when Ti elements are replaced with Ta, combined with Sn, Zn, In, La, and Bi elements to reduce the melting point and improve the structural structure, and the solder is prepared through arc smelting, multiple rolling and annealing processes.

Benefits of technology

It solves the problems of high brittleness, complex production process and high cost of Ti-containing brazing welds, realizes high-quality connection between tantalum and Q345R steel, and improves the strength, sealing and corrosion resistance of the welded joints.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119772450A_ABST
    Figure CN119772450A_ABST
Patent Text Reader

Abstract

The invention discloses AgCuNi multi-element brazing filler metal which is composed of, by mass, 5%-15% of Ni, 1%-5% of Sn, 1%-5% of Zn, 1%-5% of In, 0-1% of La, 0-1% of Bi and the balance Ag and Cu with the mass ratio being (68-76): (24-32), in addition, the invention further discloses a preparation method and a brazing process of the AgCuNi multi-element brazing filler metal, raw materials are smelted, rolled, annealed and thinned, and the AgCuNi multi-element brazing filler metal is obtained. And then the brazing filler metal, tantalum and Q345R steel are assembled into a to-be-brazed piece, and vacuum brazing is conducted on the to-be-brazed piece. The AgCuNi multi-element brazing filler metal is uniform in component, free of segregation and oxide inclusion and capable of being well combined with two kinds of base metal of tantalum and Q345R steel in the brazing process, a high-strength brazed joint is obtained, meanwhile, the brazing filler metal does not contain Ti, and the problem of weld brittleness caused by Ti is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of welding of dissimilar materials, and in particular relates to an AgCuNi multi-element solder and a preparation method and a soldering process thereof. Background Art

[0002] As a special pressure-bearing equipment, the manufacturing technology and quality of pressure vessels directly affect the development of related fields. Pressure vessels are widely used in high-tech fields, and the market size is growing year by year. The requirements for design, manufacturing and performance are increasing, and material selection has become the key. Tantalum has become the preferred material for high-performance pressure vessels due to its excellent corrosion resistance, stability, ductility and processability, but the cost is high. Q345R steel, as a commonly used material, has the characteristics of good weldability, high yield strength, good toughness and low cost. In order to reduce costs and give full play to the performance advantages of tantalum and steel, the combination of the two has become a research hotspot. However, the physical and chemical properties of the two are very different, and traditional welding methods are difficult to achieve high-quality connections.

[0003] At present, explosive welding is a method to achieve effective connection between tantalum and Q345R steel, but explosive welding has disadvantages such as complex process, high cost, and great damage to the environment. Although AgCuTi brazing filler metal prepared by powder metallurgy can achieve tantalum / Q345R steel brazing, Ti is very easy to oxidize during storage and preparation, and is extremely easy to segregate during smelting, so it can only be formed by powder metallurgy. There are problems such as complex process and relatively high production cost. In addition, the Ti element can also cause problems such as high brittleness and easy fracture of the weld.

[0004] Therefore, it is urgent to develop a Ti-free solder prepared by a smelting method. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide an AgCuNi multi-element solder in view of the above-mentioned deficiencies of the prior art. The AgCuNi multi-element solder realizes brazing connection through the reaction of Ni element and Ta, replacing the interface effect of solid solution diffusion between active element Ti and Ta, and solves the problems of high brittleness of the weld seam of Ti-containing solder, complex production process, high cost, inconvenient storage, etc.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: an AgCuNi multi-component solder, characterized in that the AgCuNi multi-component solder is composed of the following components in mass percentage: Ni 5%~15%, Sn 1%~5%, Zn 1%~5%, In 1%~5%, La 0~1%, Bi 0~1%, and the remainder is Ag and Cu, and the mass ratio of Ag to Cu is 68~76:24~32.

[0007] The AgCuNi multi-element solder of the present invention is composed of Ag, Cu, Ni, Sn, Zn, In, La and Bi elements, wherein Ag and Cu hardly produce phase change reaction with welding base materials, and connection with Ta is achieved by element diffusion or formation of intermetallic compounds with high Ni content, Sn, Zn and In play a role in improving solder structure while reducing the solder melting point, and the addition of La and Bi is beneficial to regulating alloy phase interface, improving solder wettability and strengthening weld mechanical properties, and by controlling the mass ratio of Ag and Cu to make them a eutectic component, the alloy solid phase line and liquid phase line are closest, and the fluidity and wettability are good, and the change in the silver-copper content ratio takes into account that when the Ni content increases, it can be fully dissolved in copper, thereby achieving the regulation of the melting point.

[0008] In addition, the present invention also provides a method for preparing a AgCuNi multi-element solder, characterized in that the method comprises the following steps:

[0009] Step 1: ultrasonically clean Ni, Sn, Zn, In, La, Bi, Ag and Cu metal blocks in ethanol or acetone and then dry them in an oven to obtain clean raw materials;

[0010] Step 2: repeatedly smelting the clean raw material obtained in step 1 in an arc melting furnace for more than three times to obtain an alloy ingot;

[0011] Step 3: The alloy ingot obtained in step 2 is rolled multiple times using a double-roll rolling mill, and the total deformation of the multiple rollings is less than 50%, to obtain a billet;

[0012] Step 4: annealing the blank obtained in step 3;

[0013] Step 5, repeating steps 3 and 4 multiple times to obtain a rolled material with a thickness of less than 200 μm;

[0014] Step 6: Use a precision rolling mill to reduce the thickness of the rolled material obtained in step 5 to less than 100 μm, and then use 2000-mesh sandpaper to further reduce the thickness to 60 μm to 80 μm to obtain AgCuNi multi-element solder.

[0015] The invention removes impurities on the surface of raw materials by ultrasonic cleaning and drying, repeatedly smelts more than three times, and observes whether the bottom of the alloy ingot is melted evenly during the smelting process to ensure the uniformity and quality of the alloy ingot, thereby ensuring the uniformity and quality of the AgCuNi multi-element solder, and thins the alloy ingot by rolling it for many times using a double-roll rolling mill to facilitate use, controls the deformation of the alloy ingot to ensure that it does not exceed the processing limit and avoids cracks, reduces the residual stress generated after rolling and reduces the hardness of the alloy by annealing, and gradually thins and anneals the material by repeating steps three and four for many times, recovers the processing capacity of the alloy by annealing, obtains a rolled material with a thickness of less than 200 μm, and then thins the thickness to less than 100 μm by a precision rolling mill, and further thins the AgCuNi multi-element solder with a thickness of 60 μm to 80 μm by sandpaper, thereby improving the welding performance of the alloy solder, providing a sufficient wetting area and melting amount, ensuring the strength and sealing of the welding joint, and at the same time, the solder within this thickness range can form a uniform weld during the welding process, thereby improving the welding quality.

[0016] The above method is characterized in that the mass purity of the Ni, Sn, Zn, In, La, Bi, Ag and Cu metal blocks in step 1 is not less than 99.9%. The present invention ensures the purity of the AgCuNi multi-element solder by controlling the purity of the raw materials, thereby ensuring the quality.

[0017] The above method is characterized in that the annealing process in step 4 is: in a vacuum degree less than 1×10 -3 Pa at a heating rate of 5°C / min to 10°C / min, and then annealed for 2h to 3h after heating to 600°C to 700°C. The present invention controls the annealing parameters to fully reduce the residual stress generated after rolling and reduce the hardness of the solder, thereby restoring the processing ability of the alloy and preventing the material from melting and deforming due to too high an annealing temperature and the inability to recover and recrystallize due to too low a temperature.

[0018] In addition, the present invention also provides a brazing process of AgCuNi multi-element solder, characterized in that the process comprises the following steps:

[0019] Step 1: sandwiching the AgCuNi multi-element solder between tantalum and Q345R steel to obtain a sandwich structure of a component to be brazed, which is assembled of tantalum / AgCuNi multi-element solder / Q345R steel;

[0020] Step 2: Place the brazed parts obtained in step 1 into a vacuum atmosphere tubular electric furnace and evacuate the vacuum to a temperature not greater than 5×10 -3After Pa, heat from room temperature to 600℃~700℃ at a heating rate of 5℃ / min~10℃ / min, keep warm for 5min~10min, then heat to 800℃~900℃ at a heating rate of 5℃ / min~10℃ / min, keep warm for 5min~20min, then cool to 400℃~500℃ at a cooling rate of 5℃ / min~10℃ / min, and then cool to room temperature with the furnace to complete the vacuum brazing of tantalum and Q345R steel.

[0021] The present invention sandwiches AgCuNi multi-element brazing material between tantalum and Q345R steel, so as to facilitate brazing connection between tantalum and Q345R steel. By controlling the brazing parameters and specifically controlling the vacuum to be no greater than 5×10 -3 Pa, prevent the material from oxidation, first heat to 600℃~700℃ at a heating rate of 5℃ / min~10℃ / min, keep warm for 5min~10min, avoid deformation or cracking caused by rapid heating, make the internal temperature of the parts to be brazed evenly distributed, ensure that the brazing material can be fully preheated and ready to melt, then heat to 800℃~900℃ at a heating rate of 5℃ / min~10℃ / min, keep warm for 5min~20min, make the brazing material fully melt and wet the parent material to form a strong metallurgical bond, then cool to 400℃~500℃ at a cooling rate of 5℃ / min~10℃ / min, which helps to slow down the cooling rate of the weld and reduce the risk of thermal cracks caused by rapid cooling, cool to room temperature with the furnace, ensure that the weld maintains a relatively uniform temperature gradient during the cooling process, further reduce thermal stress and deformation, and ensure the strength of brazing.

[0022] The above method is characterized in that a pressing block is placed above the workpiece to be brazed in step 1, and the pressure applied by the pressing block is 1 kPa to 3 kPa. The present invention places a pressing block and applies pressure to make the tantalum / AgCuNi multi-element brazing material / Q345R steel fully contact under the action of external force, thereby avoiding the occurrence of cold welding.

[0023] Compared with the prior art, the present invention has the following advantages:

[0024] 1. The AgCuNi multi-element solder of the present invention mainly realizes soldering connection through the reaction of Ni element and Ta, replacing the interface effect of solid solution diffusion between active element Ti and Ta, thereby solving the problems of high brittleness of the weld of Ti-containing solder, complex production process, high cost, inconvenient storage, etc. At the same time, the Ni element can also refine the solder structure, break and thin the original coarse dendrites, inhibit the generation of brittle phase, purify the grain boundary, improve the plasticity, improve the joint bonding strength, and at the same time improve the corrosion resistance and high temperature resistance of the solder.

[0025] 2. The present invention reduces the melting point of the solder and improves the weld structure through the synergistic effect of Sn, In, Zn, La, and Bi elements. Sn, Zn, and In can significantly improve the cast alloy structure of the AgCuNi multi-element solder and improve the uniformity of the alloy structure. Zn can also improve the wettability of the AgCu-based solder, reduce the melting point of the solder, and improve the strength and hardness of the joint. Adding a small amount of rare earth elements La and Bi can regulate the solder phase interface and improve the wettability, so that a welded joint with excellent performance can be obtained after brazing.

[0026] 3. The present invention adopts arc melting combined with multiple rolling, annealing and thinning methods to prepare AgCuNi multi-element solder, which has the advantages of uniform composition, no oxide inclusions, improved performance of the solder, etc., and its production process is relatively simple and low-cost, which solves the problem of segregation of the solder during the smelting process.

[0027] 4. The present invention controls the parameters of the brazing process and adopts multi-stage heating and cooling to ensure the strength of the brazing. The connection process is stable and reliable, the operation is simple, and it has important application value and is easy to promote widely.

[0028] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The present invention is a flow chart of the preparation method of AgCuNi multi-element solder and its brazing process.

[0030] Figure 2 This is the metallographic structure diagram of the AgCuNi multi-element solder obtained in Example 1 of the present invention.

[0031] Figure 3 This is a metallographic structure diagram of a brazed joint obtained by vacuum brazing tantalum and Q345R steel in Example 3 of the present invention. DETAILED DESCRIPTION

[0032] Figure 1 The present invention is a method for preparing AgCuNi multi-element solder and a flow chart of its brazing process, from Figure 1 It can be seen that ethanol or acetone is first added to the Ni, Sn, Zn, In, La, Bi, Ag and Cu metal blocks, ultrasonically cleaned and dried in an oven, and then melted into alloy ingots in an arc melting furnace. The alloy ingots are subjected to multiple rolling and annealing treatments and then thinned to obtain AgCuNi multi-element brazing filler metal. The prepared AgCuNi multi-element brazing filler metal is then assembled with tantalum and Q345R steel into a sandwich structure of parts to be brazed, and vacuum brazing is performed.

[0033] Example 1

[0034] In this embodiment, the AgCuNi multi-element solder is composed of the following components in mass percentage: Ni5%, Sn1%, Zn1%, In1%, and the remainder is Ag and Cu, and the mass ratio of Ag to Cu is 72:28.

[0035] This embodiment includes the following steps:

[0036] Step 1: ultrasonically clean Ni, Sn, Zn, In, La, Bi, Ag and Cu metal blocks with a purity of not less than 99.9% in ethanol for 15 minutes and then dry them in an oven to obtain clean raw materials;

[0037] Step 2: repeatedly smelting the clean raw material obtained in step 1 in an arc melting furnace for more than three times, and observing whether the bottom of the alloy ingot is evenly melted to obtain an alloy ingot;

[0038] Step 3: The alloy ingot obtained in step 2 is rolled multiple times using a double-roll rolling mill, and the total deformation of the multiple rollings is less than 50%, to obtain a billet;

[0039] Step 4: Place the blank obtained in step 3 under a vacuum of less than 1×10 -3 Pa at a heating rate of 5°C / min, heated to 600°C and then annealed for 3h;

[0040] Step 5: Repeat steps 3 and 4 for multiple times to obtain a rolled material with a thickness of less than 200 μm;

[0041] Step 6: Use a precision rolling mill to reduce the thickness of the rolled material obtained in step 5 to less than 100 μm, and then use 2000-mesh sandpaper to further reduce the thickness to 60 μm to obtain AgCuNi multi-element solder.

[0042] Step 7: sandwich the AgCuNi multi-element solder prepared in step 6 between tantalum and Q345R steel to obtain a sandwich structure of a soldering part assembled with tantalum / AgCuNi multi-element solder / Q345R steel, and place a pressing block on the soldering part, the pressure applied by the pressing block is 3 kPa;

[0043] Step 8: Place the brazed parts obtained in step 7 into a vacuum atmosphere tubular electric furnace and evacuate the vacuum to a temperature not greater than 5×10 -3 After Pa, it was heated from room temperature to 600°C at a heating rate of 10°C / min, kept warm for 10 minutes, then heated to 800°C at a heating rate of 5°C / min, kept warm for 15 minutes, and then cooled to 400°C at a cooling rate of 5°C / min and then cooled to room temperature with the furnace to complete the vacuum brazing of tantalum and Q345R steel.

[0044] Figure 2 The metallographic structure diagram of the AgCuNi multi-element solder obtained in this embodiment is shown in FIG. Figure 2 It can be seen that the alloy components in the AgCuNi multi-element solder obtained in this embodiment are evenly distributed, the Ag-rich phase and the Cu-rich phase are dispersedly distributed, and there is no large-area aggregation phenomenon.

[0045] After testing, it was found that the alloy components in the AgCuNi multi-element solder obtained in this embodiment were evenly distributed, the Ag-rich phase and the Cu-rich phase were dispersedly distributed, and there was no large-area aggregation phenomenon. The brazed joint interface obtained by vacuum brazing of tantalum and Q345R steel in this embodiment had no holes, cracks, etc., and the organizational structure was uniform.

[0046] Example 2

[0047] In this embodiment, the AgCuNi multi-element solder is composed of the following components in mass percentage: Ni8%, Sn2%, Zn3%, In3%, La0.5%, Bi0.5%, and the remainder is Ag and Cu, and the mass ratio of Ag to Cu is 72:28.

[0048] This embodiment includes the following steps:

[0049] Step 1: ultrasonically clean Ni, Sn, Zn, In, La, Bi, Ag and Cu metal blocks with a purity of not less than 99.9% in acetone for 20 minutes and then dry them in an oven to obtain clean raw materials;

[0050] Step 2: repeatedly smelting the clean raw material obtained in step 1 in an arc melting furnace for more than three times, and observing whether the bottom of the alloy ingot is evenly melted to obtain an alloy ingot;

[0051] Step 3: The alloy ingot obtained in step 2 is rolled multiple times using a double-roll rolling mill, and the total deformation of the multiple rollings is less than 50%, to obtain a billet;

[0052] Step 4: Place the blank obtained in step 3 under a vacuum of less than 1×10 -3 Pa, heated to 700 °C at a heating rate of 10 °C / min and then annealed for 2 h;

[0053] Step 5: Repeat steps 3 and 4 for multiple times to obtain a rolled material with a thickness of less than 200 μm;

[0054] Step 6: Use a precision rolling mill to reduce the thickness of the rolled material obtained in step 5 to less than 100 μm, and then use 2000-mesh sandpaper to further reduce the thickness to 60 μm to obtain AgCuNi multi-element solder.

[0055] Step 7: sandwich the AgCuNi multi-element solder prepared in step 6 between tantalum and Q345R steel to obtain a sandwich structure of a workpiece to be brazed assembled from tantalum / AgCuNi multi-element solder / Q345R steel, and place a pressing block on the workpiece to be brazed, the pressure applied by the pressing block is 2 kPa;

[0056] Step 8: Place the brazed parts obtained in step 7 into a vacuum atmosphere tubular electric furnace and evacuate the vacuum to a temperature not greater than 5×10 -3 After Pa, it was heated from room temperature to 600°C at a heating rate of 10°C / min, kept warm for 10 min, then heated to 900°C at a heating rate of 5°C / min, kept warm for 15 min, cooled to 400°C at a cooling rate of 5°C / min, and then cooled to room temperature with the furnace to complete the vacuum brazing of tantalum and Q345R steel.

[0057] After testing, it was found that the alloy components in the AgCuNi multi-element solder obtained in this embodiment were evenly distributed, the Ag-rich phase and the Cu-rich phase were dispersedly distributed, and there was no large-area aggregation phenomenon. The brazed joint interface obtained by vacuum brazing of tantalum and Q345R steel in this embodiment had no holes, cracks, etc., and the organizational structure was uniform.

[0058] Example 3

[0059] In this embodiment, the AgCuNi multi-element solder is composed of the following components in mass percentage: Ni 10%, Sn 3%, Zn 4%, In 3%, La 0.4%, Bi 0.4%, and the remainder is Ag and Cu, and the mass ratio of Ag to Cu is 72:28.

[0060] This embodiment includes the following steps:

[0061] Step 1: ultrasonically clean Ni, Sn, Zn, In, La, Bi, Ag and Cu metal blocks with a purity of not less than 99.9% in ethanol for 20 minutes and then dry them in an oven to obtain clean raw materials;

[0062] Step 2: repeatedly smelting the clean raw material obtained in step 1 in an arc melting furnace for more than three times, and observing whether the bottom of the alloy ingot is evenly melted to obtain an alloy ingot;

[0063] Step 3: The alloy ingot obtained in step 2 is rolled multiple times using a double-roll rolling mill, and the total deformation of the multiple rollings is less than 50%, to obtain a billet;

[0064] Step 4: Place the blank obtained in step 3 under a vacuum of less than 1×10 -3 Pa at a heating rate of 8°C / min, heated to 650°C and then annealed for 2.5h;

[0065] Step 5, repeating steps 3 and 4 multiple times to obtain a rolled material with a thickness of less than 200 μm;

[0066] Step 6: Use a precision rolling mill to reduce the thickness of the rolled material obtained in step 5 to less than 100 μm, and then use 2000-mesh sandpaper to further reduce the thickness to 60 μm to obtain AgCuNi multi-element solder.

[0067] Step 7: sandwich the AgCuNi multi-element solder prepared in step 6 between tantalum and Q345R steel to obtain a sandwich structure of a soldering part assembled with tantalum / AgCuNi multi-element solder / Q345R steel, and place a pressing block on the soldering part, the pressure applied by the pressing block is 3 kPa;

[0068] Step 8: Place the brazed parts obtained in step 7 into a vacuum atmosphere tubular electric furnace and evacuate the vacuum to a temperature not greater than 5×10 -3 After Pa, it was heated from room temperature to 600°C at a heating rate of 10°C / min, kept warm for 10 minutes, then heated to 850°C at a heating rate of 5°C / min, kept warm for 15 minutes, and then cooled to 400°C at a cooling rate of 5°C / min and then cooled to room temperature with the furnace to complete the vacuum brazing of tantalum and Q345R steel.

[0069] Figure 3 The metallographic structure diagram of the brazed joint obtained by vacuum brazing of tantalum and Q345R steel in this embodiment is as follows: Figure 3 It can be seen that the brazing seam interface obtained by vacuum brazing of tantalum and Q345R steel in this embodiment has no holes, cracks, etc., and the organizational structure is uniform.

[0070] After testing, it was found that the alloy components in the AgCuNi multi-element solder obtained in this embodiment were evenly distributed, the Ag-rich phase and the Cu-rich phase were dispersedly distributed, and there was no large-area aggregation phenomenon. The brazed joint interface obtained by vacuum brazing of tantalum and Q345R steel in this embodiment had no holes, cracks, etc., and the organizational structure was uniform.

[0071] Example 4

[0072] In this embodiment, the AgCuNi multi-element solder is composed of the following components in mass percentage: Ni 15%, Sn 5%, Zn 5%, In 5%, La 1%, Bi 1%, and the remainder is Ag and Cu, and the mass ratio of Ag to Cu is 72:28.

[0073] This embodiment includes the following steps:

[0074] Step 1: ultrasonically clean Ni, Sn, Zn, In, La, Bi, Ag and Cu metal blocks with a purity of not less than 99.9% in ethanol for 15 minutes and then dry them in an oven to obtain clean raw materials;

[0075] Step 2: repeatedly smelting the clean raw material obtained in step 1 in an arc melting furnace for more than three times, and observing whether the bottom of the alloy ingot is evenly melted to obtain an alloy ingot;

[0076] Step 3: The alloy ingot obtained in step 2 is rolled multiple times using a double-roll rolling mill, and the total deformation of the multiple rollings is less than 50%, to obtain a billet;

[0077] Step 4: Place the blank obtained in step 3 under a vacuum of less than 1×10 -3 Pa at a heating rate of 5°C / min, heated to 700°C and then annealed for 2.5h;

[0078] Step 5: Repeat steps 3 and 4 for multiple times to obtain a rolled material with a thickness of less than 200 μm;

[0079] Step 6: Use a precision rolling mill to reduce the thickness of the rolled material obtained in step 5 to less than 100 μm, and then use 2000-mesh sandpaper to further reduce the thickness to 60 μm to obtain AgCuNi multi-element solder.

[0080] Step 7: sandwich the AgCuNi multi-element solder prepared in step 6 between tantalum and Q345R steel to obtain a sandwich structure of a soldering part assembled with tantalum / AgCuNi multi-element solder / Q345R steel, and place a pressing block on the soldering part, the pressure applied by the pressing block is 1 kPa;

[0081] Step 8: Place the brazed parts obtained in step 7 into a vacuum atmosphere tubular electric furnace and evacuate the vacuum to a temperature not greater than 5×10 -3 After Pa, it was heated from room temperature to 600℃ at a heating rate of 10℃ / min, kept warm for 10min, then heated to 880℃ at a heating rate of 5℃ / min, kept warm for 15min, cooled to 400℃ at a cooling rate of 5℃ / min, and then cooled to room temperature with the furnace to complete the vacuum brazing of tantalum and Q345R steel.

[0082] After testing, it was found that the alloy components in the AgCuNi multi-element solder obtained in this embodiment were evenly distributed, the Ag-rich phase and the Cu-rich phase were dispersedly distributed, and there was no large-area aggregation phenomenon. The brazed joint interface obtained by vacuum brazing of tantalum and Q345R steel in this embodiment had no holes, cracks, etc., and the organizational structure was uniform.

[0083] The brazed joints obtained by vacuum brazing of tantalum and Q345R steel in Examples 1 to 4 were subjected to a tensile shear strength test. The results are shown in Table 1.

[0084] Table 1

[0085] Example 1 Example 2 Example 3 Example 4 136.44MPa 167.37MPa 143.21MPa 138.69MPa

[0086] It can be seen from Table 1 that the AgCuNi multi-element brazing filler metals designed in Examples 1 to 4 are used for vacuum brazing of tantalum and Q345R steel, and the tensile shear strength of the obtained brazed joints is not less than 130 MPa.

[0087] Example 5

[0088] In this embodiment, the AgCuNi multi-element solder is composed of the following components in mass percentage: Ni 15%, Sn 5%, Zn 5%, In 5%, La 1%, Bi 1%, and the remainder is Ag and Cu, and the mass ratio of Ag to Cu is 68:32.

[0089] This embodiment includes the following steps:

[0090] Step 1: ultrasonically clean Ni, Sn, Zn, In, La, Bi, Ag and Cu metal blocks with a purity of not less than 99.9% in ethanol for 15 minutes and then dry them in an oven to obtain clean raw materials;

[0091] Step 2: repeatedly smelting the clean raw material obtained in step 1 in an arc melting furnace for more than three times, and observing whether the bottom of the alloy ingot is evenly melted to obtain an alloy ingot;

[0092] Step 3: The alloy ingot obtained in step 2 is rolled multiple times using a double-roll rolling mill, and the total deformation of the multiple rollings is less than 50%, to obtain a billet;

[0093] Step 4: Place the blank obtained in step 3 under a vacuum of less than 1×10 -3 Pa at a heating rate of 5°C / min, heated to 700°C and then annealed for 2.5h;

[0094] Step 5: Repeat steps 3 and 4 for multiple times to obtain a rolled material with a thickness of less than 200 μm;

[0095] Step 6: Use a precision rolling mill to reduce the thickness of the rolled material obtained in step 5 to less than 100 μm, and then use 2000-mesh sandpaper to further reduce the thickness to 80 μm to obtain AgCuNi multi-element solder.

[0096] Step 7: sandwich the AgCuNi multi-element solder prepared in step 6 between tantalum and Q345R steel to obtain a sandwich structure of a workpiece to be brazed assembled from tantalum / AgCuNi multi-element solder / Q345R steel, and place a pressing block on the workpiece to be brazed, the pressure applied by the pressing block is 2 kPa;

[0097] Step 8: Place the brazed parts obtained in step 7 into a vacuum atmosphere tubular electric furnace and evacuate the vacuum to a temperature not greater than 5×10 -3After Pa, it was heated from room temperature to 650°C at a heating rate of 5°C / min, kept warm for 8min, then heated to 840°C at a heating rate of 8°C / min, kept warm for 20min, cooled to 500°C at a cooling rate of 10°C / min, and then cooled to room temperature with the furnace to complete the vacuum brazing of tantalum and Q345R steel.

[0098] After testing, it was found that the alloy components in the AgCuNi multi-element solder obtained in this embodiment were evenly distributed, the Ag-rich phase and the Cu-rich phase were dispersedly distributed, and there was no large-area aggregation phenomenon. The brazed joint interface obtained by vacuum brazing of tantalum and Q345R steel in this embodiment had no holes, cracks, etc., and the organizational structure was uniform.

[0099] Example 6

[0100] In this embodiment, the AgCuNi multi-element solder is composed of the following components in mass percentage: Ni 15%, Sn 5%, Zn 5%, In 2%, La 1%, Bi 1%, and the remainder is Ag and Cu, and the mass ratio of Ag to Cu is 76:24.

[0101] This embodiment includes the following steps:

[0102] Step 1: ultrasonically clean Ni, Sn, Zn, In, La, Bi, Ag and Cu metal blocks with a purity of not less than 99.9% in ethanol for 15 minutes and then dry them in an oven to obtain clean raw materials;

[0103] Step 2: repeatedly smelting the clean raw material obtained in step 1 in an arc melting furnace for more than three times, and observing whether the bottom of the alloy ingot is evenly melted to obtain an alloy ingot;

[0104] Step 3: The alloy ingot obtained in step 2 is rolled multiple times using a double-roll rolling mill, and the total deformation of the multiple rollings is less than 50%, to obtain a billet;

[0105] Step 4: Place the blank obtained in step 3 under a vacuum of less than 1×10 -3 Pa at a heating rate of 5°C / min, heated to 700°C and then annealed for 2.5h;

[0106] Step 5, repeating steps 3 and 4 multiple times to obtain a rolled material with a thickness of less than 200 μm;

[0107] Step 6: Use a precision rolling mill to reduce the thickness of the rolled material obtained in step 5 to less than 100 μm, and then use 2000-mesh sandpaper to further reduce the thickness to 70 μm to obtain AgCuNi multi-element solder.

[0108] Step 7: sandwich the AgCuNi multi-element solder prepared in step 6 between tantalum and Q345R steel to obtain a sandwich structure of a workpiece to be brazed assembled from tantalum / AgCuNi multi-element solder / Q345R steel, and place a pressing block on the workpiece to be brazed, the pressure applied by the pressing block is 2 kPa;

[0109] Step 8: Place the brazed parts obtained in step 7 into a vacuum atmosphere tubular electric furnace and evacuate the vacuum to a temperature not greater than 5×10 -3 After Pa, it was heated from room temperature to 700℃ at a heating rate of 8℃ / min, kept warm for 5min, then heated to 850℃ at a heating rate of 10℃ / min, kept warm for 5min, cooled to 450℃ at a cooling rate of 8℃ / min, and then cooled to room temperature with the furnace to complete the vacuum brazing of tantalum and Q345R steel.

[0110] After testing, it was found that the alloy components in the AgCuNi multi-element solder obtained in this embodiment were evenly distributed, the Ag-rich phase and the Cu-rich phase were dispersedly distributed, and there was no large-area aggregation phenomenon. The brazed joint interface obtained by vacuum brazing of tantalum and Q345R steel in this embodiment had no holes, cracks, etc., and the organizational structure was uniform.

[0111] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. An AgCuNi multi-element solder, characterized in that: The AgCuNi multi-element solder consists of the following components in mass percentage: Ni 5%-15%, Sn 1%-5%, Zn 1%-5%, In 1%-5%, La 0-1%, Bi 0-1%, and the remainder is Ag and Cu, and the mass ratio of Ag to Cu is 68-76:24-32.

2. A method for preparing the AgCuNi multi-element solder as claimed in claim 1, characterized in that: The method comprises the following steps: Step 1: ultrasonically clean Ni, Sn, Zn, In, La, Bi, Ag and Cu metal blocks in ethanol or acetone and then dry them in an oven to obtain clean raw materials; Step 2: repeatedly smelting the clean raw material obtained in step 1 in an arc melting furnace for more than three times to obtain an alloy ingot; Step 3: The alloy ingot obtained in step 2 is rolled multiple times using a double-roll rolling mill, and the total deformation of the multiple rollings is less than 50%, to obtain a billet; Step 4: annealing the blank obtained in step 3; Step 5, repeating steps 3 and 4 multiple times to obtain a rolled material with a thickness of less than 200 μm; Step 6: Use a precision rolling mill to reduce the thickness of the rolled material obtained in step 5 to less than 100 μm, and then use 2000-mesh sandpaper to further reduce the thickness to 60 μm to 80 μm to obtain AgCuNi multi-element solder.

3. The method according to claim 2, characterized in that The mass purity of the Ni, Sn, Zn, In, La, Bi, Ag and Cu metal blocks described in step 1 is not less than 99.9%.

4. The method according to claim 2, characterized in that: The annealing process in step 4 is as follows: -3 Under the condition of Pa, the temperature is increased at a rate of 5°C / min to 10°C / min to 600°C to 700°C, and then annealed for 2h to 3h.

5. A brazing process for the AgCuNi multi-element solder prepared as claimed in any one of claims 2 to 4, characterized in that: The process includes the following steps: Step 1: sandwiching the AgCuNi multi-element solder between tantalum and Q345R steel to obtain a sandwich structure of a component to be brazed, which is assembled of tantalum / AgCuNi multi-element solder / Q345R steel; Step 2: Place the brazed parts obtained in step 1 into a vacuum atmosphere tubular electric furnace and evacuate the vacuum to a temperature not greater than 5×10 -3 After Pa, heat from room temperature to 600℃~700℃ at a heating rate of 5℃ / min~10℃ / min, keep warm for 5min~10min, then heat to 800℃~900℃ at a heating rate of 5℃ / min~10℃ / min, keep warm for 5min~20min, then cool to 400℃~500℃ at a cooling rate of 5℃ / min~10℃ / min, and then cool to room temperature with the furnace to complete the vacuum brazing of tantalum and Q345R steel.

6. The method according to claim 5, characterized in that In step 1, a pressing block is placed above the parts to be brazed, and the pressure applied by the pressing block is 1 kPa to 3 kPa.

Citation Information

Patent Citations

  • Pb-free solder alloy compositions comprising essentially tin (SN), silver (AG), copper (CU), nickel (NI), phosphorus (p) and / or rare earth: cerium (CE) or lanthanum (LA)

    CA2540486A1

  • Method for preparing titanium based solder

    CN101352787A

  • Polybasic silver solder

    CN103111770A

  • Solder used for vacuum active brazing process of W-Cu composite material and stainless steel and method

    CN105618957A

  • Electroforming method of silver solder with high tin content

    CN106392384A

Cited By

  • Lanthanum-containing silver alloy and preparation method and application thereof

    CN120989450A